2014
DOI: 10.1145/2629489
|View full text |Cite
|
Sign up to set email alerts
|

Wikidata

Abstract: This collaboratively edited knowledgebase provides a common source of data for Wikipedia, and everyone else.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
422
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 2,165 publications
(429 citation statements)
references
References 14 publications
0
422
0
7
Order By: Relevance
“…Table 10 shows anecdotal samples for illustration. [7], NELL [9], BabelNet [39] and Wikidata [54] extract SPO facts from Wikipedia and other sources. However, all of these are limited to a prespecified set of predicates: a few hundred in some, up to a few thousand in Freebase and Wikidata.…”
Section: Methods Under Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 10 shows anecdotal samples for illustration. [7], NELL [9], BabelNet [39] and Wikidata [54] extract SPO facts from Wikipedia and other sources. However, all of these are limited to a prespecified set of predicates: a few hundred in some, up to a few thousand in Freebase and Wikidata.…”
Section: Methods Under Comparisonmentioning
confidence: 99%
“…Knowledge bases (KBs) contain subject-predicate-object triples about entities and their properties. Popular KBs include DBpedia [2], Yago [51], Wikidata [54] and Freebase [7]. Their commercial counterparts at Google, Microsoft, Baidu, and others, provide Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge graphs such as DBpedia [2], Yago [16] and WikiData [25] as well as similar industrial initiatives by Google, Bing, IBM, BBC, or Thomson Reuters have demonstrated that representing encyclopedic and factual knowledge using RDF and Linked Data is feasible.…”
Section: Related Workmentioning
confidence: 99%
“…Since Wikipedia infoboxes are partially populated through templates from Wikidata entries, extracting data from infoboxes instead of Wikidata itself adds an additional source of errors. Furthermore, unless all language versions of Wikipedia are used as a source, such an approach would even limit the amount of retrieved information due to Wikidata's inherent multi-lingual design as the knowledge base behind all Wikipedias (Vrandeĉić and Krötzsch 2014).…”
Section: Related Workmentioning
confidence: 99%